Autophagy determines mtDNA copy number dynamics during starvation. Issue 1 (2nd January 2019) - Medeiros, Tania Catarina; Graef, Martin
ABSTRACT: Derived from bacterial ancestors, mitochondria have maintained their own albeit strongly reduced genome, mitochondrial DNA (mtDNA), which encodes for a small and highly specialized set of genes. MtDNA exists in tens to thousands of copies packaged in numerous nucleoprotein complexes, termed nucleoids, distributed throughout the dynamic mitochondrial network. Our understanding of the mechanisms of how cells regulate the copy number of mitochondrial genomes has been limited. Here, we summarize and discuss our recent findings that Mip1/POLG (mitochondrial DNA polymerase gamma) critically controls mtDNA copy number by operating in 2 opposing modes, synthesis and, unexpectedly, degradation of mtDNA, when yeast cells face nutrient starvation. The balance of the 2 modes of Mip1/POLG and thus mtDNA copy number dynamics depends on the integrity of macroautophagy/autophagy, which sustains continuous synthesis and maintenance of mtDNA. In autophagy-deficient cells, a combination of nucleotide insufficiency and elevated mitochondrial ROS production impairs mtDNA synthesis and drives mtDNA degradation by the 3ʹ-5ʹ-exonuclease activity of Mip1/POLG resulting in mitochondrial genome depletion and irreversible respiratory deficiency. Abbrivations: mtDNA: mitochondrial DNA; mtDCN: mitochondrial DNA copy number.